2009
DOI: 10.1016/j.jtcvs.2008.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Open versus endovascular repair of traumatic aortic rupture: A systematic review

Abstract: ES appears widely applicable as an emergency treatment and simplifies the treatment of other injuries. ES should be viewed as the treatment of choice for TAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Endovascular aortic repair also requires considerably less time and can be done expeditiously in relatively unstable patients. A systematic review by Akowuah and colleagues 22 showed that operative mortality and postoperative paraplegia rates were significantly less for thoracic endografting compared with open surgical repair (7% vs 19% [P < .01] and 1% vs 6% [P < .01], respectively). Nevertheless, the authors stressed that long-term outcomes are poorly documented.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular aortic repair also requires considerably less time and can be done expeditiously in relatively unstable patients. A systematic review by Akowuah and colleagues 22 showed that operative mortality and postoperative paraplegia rates were significantly less for thoracic endografting compared with open surgical repair (7% vs 19% [P < .01] and 1% vs 6% [P < .01], respectively). Nevertheless, the authors stressed that long-term outcomes are poorly documented.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of treatments of BAIs by Akowuah, 10 articles including 262 patients were identified (153 patients undergoing surgical repair and 109 endovascular repair). Postoperative results showed a higher paraplegia rate and a greater mortality rate in the surgical repair group (1% vs. 6% and 7% vs. 19%, respectively) ( 18 ). However, the mortality associated with open repair varies from one study to another and has been reported to be as low as 5% with no case of paraplegia in a previous local report ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…TEVAR for ATAI was used initially in high‐risk multiple injuries or elderly patients, but in many centers it has now become the initial procedure of choice, even in young or low‐risk patients. TEVAR appears to lower mortality and morbidity rates in patients with ATAI [8, 27, 28]. Moreover, TEVAR has extended operative treatment to those patients not previously considered candidates for repair [29].…”
Section: Discussionmentioning
confidence: 99%